Penyertaan Modal Pemerintah Daerah, Digitalisasi dan Kinerja Bank: Bukti Empiris dari Bank Pembangunan Daerah di Indonesia - Retnaning Wulan; Ayif Fathurrahman; Ahmad Maruf (JURNAL MANAJEMEN MOTIVASI, 2026)
Regional government equity participation is a policy instrument to strengthen the role of Regional Development Banks (BPD) in supporting regional economic development. However, its effectiveness varies across BPDs, depending on their internal conditions, one of which is digitalization. This study aims to analyze the impact of regional government equity participation and digitalization on BPD performance and examine the role of digitalization in strengthening this role. The results show that regional government equity participation has a positive contribution to improving bank performance, and digitalization strengthens this role. These findings indicate that equity participation and digitalization together play a significant role in supporting the strengthening of BPD performance. Keywords: Local Government Capital Injections; Bank Digitalization; Bank Performance; Regional Development Bank